2020
DOI: 10.1016/s2214-109x(20)30060-7
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in sexual activity and demand for and use of modern contraceptive methods in 74 countries: a retrospective analysis of nationally representative surveys

Abstract: Background A quarter of a century ago, two global events-the International Conference on Population and Development in Cairo, and the Fourth World Conference on Women in Beijing-placed gender equality and reproductive health and rights at the centre of the development agenda. Progress towards these goals has been slower than hoped. We used survey data and national-level indicators of social determinants from 74 countries to examine change in satisfaction of contraceptive need from a contextual perspective. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 27 publications
(20 reference statements)
5
50
0
Order By: Relevance
“…A higher prevalence of contraceptive measures is found among women who have more knowledge, awareness, and media exposure (41)(42). Our ndings are consistent with these studies as those women (aged who have greater media exposure have more knowledge about contraceptive measures, and among them the use of contraceptives measures is also more likely (48). Ethnicity is also signi cantly associated with ever-use of contraceptive measures (43).…”
Section: Discussionsupporting
confidence: 88%
“…A higher prevalence of contraceptive measures is found among women who have more knowledge, awareness, and media exposure (41)(42). Our ndings are consistent with these studies as those women (aged who have greater media exposure have more knowledge about contraceptive measures, and among them the use of contraceptives measures is also more likely (48). Ethnicity is also signi cantly associated with ever-use of contraceptive measures (43).…”
Section: Discussionsupporting
confidence: 88%
“…In our ndings, compared with adolescent married ever users aged 15-19 years old, married women aged [25][26][27][28][29][30][31][32][33][34], and 45-49 years old who were ever users had greater odds of not currently using a modern FP method. This nding corroborates the data from the Population Reference Bureau, which revealed that the reasons for not using the FP method among married individuals varied according to age.…”
Section: Discussionmentioning
confidence: 96%
“…The ndings from this study suggest that addressing unmet FP need is crucial to increasing the use of contraceptive methods among speci c groups of women who are exposed to the risk of pregnancy. Although a recent study in 78 countries showed that gender equality and education increase access to modern contraceptive methods [27], it is important to note that adapted and targeted strategies according to the speci c categories of women could yield a more sustainable increase in the demand for contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…4 Using an in-depth retrospective regression and principal component analysis, Emma Slaymaker and colleagues have provided harmonised nationally available data from 74 countries to evaluate progress on the ICPD agenda using a broader social context than just contraceptive targets, including life events such as age of sexual initiation, first union (cohabitation or marriage), and first birth; sexual behaviour; and social and economic indicators, such as gross domestic product (GDP) per capita, indices of gender development and inequality, and female and male expected years of education. 5 This study provides useful insights by using a comprehensive approach, underscoring continuing societal changes that affect the length of time after sexual initiation to first union and first birth, which can lead to additional time using modern methods of contraception. Although only at the national level, data on sexual activity, demand for contraception, and use of contraception were correlated with the gender development index and expected years of education for females in the 67 countries with data available.…”
Section: Patchy Progress On the Icpd: Are We Asking The Right Questions?mentioning
confidence: 98%